VD_FINDINFO HC / 2012 / 257 vom 24. April 2012 - VD Tribunal cantonal (2012)
DIVORCE, PROTECTION DE L'ENFANT, RETRAIT DU DROIT DE GARDE, MESURE PROVISIONNELLE | 134 al. 1 CC, 134 al. 3 CC, 310 al. 1 CC, 315b CC, 276 al. 1 CPC (CH), 296 CPC (CH), 308 al. 1 let. b CPC (CH)